2002
DOI: 10.1037/0012-1649.38.4.492
|View full text |Cite
|
Sign up to set email alerts
|

Contextual determinants of mothers' interventions in young children's peer interactions.

Abstract: In this study, the role of context in mothers' interventions in their preschool children's peer relationship problems was investigated. Event theme (aggression, peer rebuff, or initiating play), the child's role in the event (actor or target), the child's age and sex, and the mother's emotional reaction were examined as predictors of the extent to which mothers (N = 71) said they would discuss peer relationships, encourage peer interaction, and use power assertion in response to a series of videotaped vignette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 32 publications
3
26
1
Order By: Relevance
“…In their work on parental opinions about children who were depicted in text as expressing aggression, Mills and Rubin (1990) found that parents showed greater acceptance of anger expressions in boys. However, other work on parental attitudes toward children's misbehavior in problematic situations (Colwell et al, 2002;Werner et al, 2006) did not find differences with child gender. Overall, findings of research on adults' responses to children's expressions of anger are quite mixed though there appears a pattern, whereby boys' anger is treated with greater acceptance, yet harsher methods of discipline (Kerig, Cowan, & Cowan, 1993;Radke-Yarrow & Kochanska, 1990).…”
Section: Child Gender As a Contributor To Adults' Perceptionsmentioning
confidence: 84%
See 2 more Smart Citations
“…In their work on parental opinions about children who were depicted in text as expressing aggression, Mills and Rubin (1990) found that parents showed greater acceptance of anger expressions in boys. However, other work on parental attitudes toward children's misbehavior in problematic situations (Colwell et al, 2002;Werner et al, 2006) did not find differences with child gender. Overall, findings of research on adults' responses to children's expressions of anger are quite mixed though there appears a pattern, whereby boys' anger is treated with greater acceptance, yet harsher methods of discipline (Kerig, Cowan, & Cowan, 1993;Radke-Yarrow & Kochanska, 1990).…”
Section: Child Gender As a Contributor To Adults' Perceptionsmentioning
confidence: 84%
“…In a study where parents were provided with text depictions of children demonstrating aggressive and socially withdrawn behaviors, Mills and Rubin (1990) found that in comparison with children's shy behaviors, aggressive behaviors elicited mothers' greater endorsements for interventions involving power assertion (Mills & Rubin, 1990). Using a paradigm in which mothers were presented with videotaped vignettes of preschoolers involved in common peer relationship problems, Colwell and associates (Colwell, Mize, Pettit, & Laird, 2002) found that when a child had been presented as the instigator, rather than victim, of aggression, mothers reported greater approval of management strategies involving power assertion. A third study (Werner, Senich, & Przepyszny, 2006), which explored maternal reactions to text depictions of preschoolers in problematic situations with peers which involved physical and relational aggression, found that children's physical aggression was again associated with mothers' greater endorsements for power assertion.…”
Section: Contextual Determinants Of Adults' Perceptions Of Child Miscmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, when the qualities (dimensions) of mothers' reactions (intervention strategies) in relational and physical aggression situations were examined using the hypothetical vignettes, mothers were more likely to use power assertion 7 (Colwell et al, 2002;Werner et al, 2006), rule violation strategies 8 (Werner et al, 2006) and discussion 9 (Colwell et al, 2002) for children's OA than for children's RA. However, mothers used encouragement strategies 10 more frequently for children's RA than OA (Colwell et al, 2002). Mothers were more likely to inhibit children's OA by using their power.…”
Section: Mothers' Reactions and Children's Aggressionmentioning
confidence: 99%
“…Several studies on mothers' reactions to children's socially unskilled behavior showed that mothers' reactions differed according to the forms of misbehavior (Colwell, Mize, Pettit, & Laird, 2002;Harnish, 2011;Hasting & Rubin, 1999;Jung, 2003;Werner et al, 2006). In particular, when the qualities (dimensions) of mothers' reactions (intervention strategies) in relational and physical aggression situations were examined using the hypothetical vignettes, mothers were more likely to use power assertion 7 (Colwell et al, 2002;Werner et al, 2006), rule violation strategies 8 (Werner et al, 2006) and discussion 9 (Colwell et al, 2002) for children's OA than for children's RA.…”
Section: Mothers' Reactions and Children's Aggressionmentioning
confidence: 99%